Kelola Sampah Dapur Rumah Tangga Menjadi Eco-Enzym Serbaguna dan Ramah Lingkungan - Mariyati, Umi; Anindita, Devina Cinantya; Tafakresnanto, Chendy; Widiyono, Wahyu (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2024)
Garbage is unused residual waste originating from households and industry. Organic Garbage is residual waste that has not been used by households or industry. Organic waste originating from households is not managed correctly, causing problems in the form of unpleasant odors and the emergence of disease. Proper management of household organic waste can have a positive impact, one of which is processing it into multi-purpose Eco-enzymes. Eco-enzyme is an organic solution from organic waste that has gone through the fermentation phase and has various benefits for the surrounding environment. Processing household kitchen waste into Eco-enzyme aims to manage household kitchen waste into Eco-enzyme by involving farmer groups in Kebonagung Village, Ploso District, Jombang Regency. This household kitchen waste processing activity were carried out at the place of one of the farmer group members. Household kitchen waste that was managed includes leftover vegetables and fruit that are not consumed but are not rotten. The process of making Eco-enzyme uses fruit and vegetable waste put in a drinking water container, then adding brown sugar and water according to the ratio (sugar: vegetable and fruit waste: water) 1:3:10. Benefits of Eco-enzyme made by the Patoman farmer group as organic fertilizer, polluted water purifier, and household appliance cleaner. Sampah merupakan limbah sisa yang sudah tidak dimanfaatkan yang berasal dari rumah tangga maupun industri. Sampah organik yang berasal dari rumah tangga tidak banyak dikelola dengan tepat sehingga menimbulkan masalah yaitu berupa aroma tidak sedap dan timbulya penyakit. Pengelolaan sampah organik rumah tangga yang tepat dapat memberikan dampak positif salah satunya adalah pengolahan menjadi Eco-enzym serbaguna. Eco-enzym merupakan larutan organik yang berasal dari sampah organik yang telah melewati fase fernentasi dan memiliki berbagai manfaat baik bagi lingkungan sekitar. Pengolahan sampah dapur rumah tangga menjadi Eco-enzym bertujuan untuk mengelola limbah dapur rumah tangga menjadi Eco-enzym dengan melibatkan kelompok tani yang berada di Desa Kebonagung, Kecamatan Ploso, Kabupaten Jombang. Kegiatan pengolahan limbah dapur rumah tangga dilaksanakan ditempat salah satu anggota kelompok tani. Limbah dapur rumah tangga yang dikelola antara lain sisa sayuran dan buah-buahan yang tidak dikonsumsi namun tidak busuk. Proses pembuatan Eco-enzym menggunakan sisa buah dan sayur dimasukkan ke dalam wadah bekas air minuman kemudian diberi gula merah dan air sesuai dengan perbandingan (gula:sisa sayuran dan buah:air) 1:3:10. Manfaat Eco-enzym yang dibuat oleh kelompok tani Patoman sebagai pupuk organik, bahan penjernih air yang tercemar dan pemberish alat rumah tangga.